Seasonal Variability of Water Quality and Water Management Strategies in Karang Agung Hilir Swampland - Insanul Kamil; Yogi Agus Stiawan; Kasiyanti Kasiyanti (JURNAL TEKNIK HIDRAULIK, 2025)
To increase food production in the Karang Agung Hilir Swampland requires effective water management by understanding the hydrodynamics of water quantity and quality; however, related research remains limited. This study aims to examine the characteristics of the Karang Agung Hilir Swampland in relation to tidal variability and water quality. The method used is correlation analysis with the variables of tidal hydrodynamics, land elevation, pH, electrical conductivity (EC), and salinity in the rainy and dry seasons. . Tidal influence is significant at the channel estuary but decreases toward the channel’s end. The land in the middle of the navigation channel is classified as hydro-topography A (<+2.00 m), B (+2.00 m to +2.30 m), and C (>+2.30 m). During the rainy season, the pH in the estuary and mid-channel is higher during spring tide than during neap tide, influenced by elevated EC values indicating saltwater intrusion during high tides. At the channel’s end, extremely acidic pH (<4.00) and EC values exceeding 2,000 µS/cm suggest the presence of an oxidized pyrite layer. In the dry season, pH levels in the channel are higher compared to the rainy season due to increased salt concentrations. Water management strategies are needed to enhance acid leaching, prevent pyrite oxidation, and limit saltwater intrusion. A one-way water management system is recommended to improve water circulation and supply, while maintaining water levels above the pyrite layer. This research is expected to provide recommendations for water management in swamplands with similar characteristics to this research location.